Integrated assessment of the sustainability and resilience of farming systems: Lessons from the past and ways forward for the future - Francesco Accatino; Wim Paas; Hugo Herrera; Corentin Pinsard; Simone Severini; Franziska Appel; Birgit Kopainsky; Katarzyna Bańkowska; Jo Bijttebier; Camelia Gavrilescu; Amr Khafagy; Vitaliy Krupin; et al. (Resilient and sustainable farming systems in Europe: Exploring diversity and pathways, 2022)
This chapter assessed sustainability and resilience of eleven farming systems in their current situation, as well as in hypothetical future systems, using qualitative and quantitative methods. The assessment shows that current farming systems address sustainability dimensions in an unbalanced way and are characterized by poor resilience. Future resilient systems are imagined to promote environmental and social functions in the long term.
Keywords: 330; farming system; resilience; sustainability; functions; challenges; strategies; resilience capacities; resilience attributes